1994
DOI: 10.1177/009102609402300209
|View full text |Cite
|
Sign up to set email alerts
|

Violence in the Workplace: The Role of Human Resource Management

Abstract: An upset individual walks into the Department of Human Resource Management and demands to see the Director. He explains to the receptionist that the recent Reduction-in-force within the organization left him without a job, and with a wife and two children who are depending on him for support. He is clearly emotionally upset, and, when the receptionist informs him that he will have to make an appointment and come back at a later time, he pulls out a gun, shoots the receptionist and two personnel clerks in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 3 publications
0
15
0
2
Order By: Relevance
“…It is suggested that work-related violent acts are vastly understated since, in many cases, the figures do not reflect verbal, indirect and passive forms of aggression which are, in fact, more pervasive. [12][13][14] In the UK only those incidents which involve physical violence resulting in at least three days' absence from work are reportable. 15 Keyes and Heim 16 suggest that ambiguous incidents such as an employee who is berated in front of peers, sabotaged machinery which unintentionally injures an employee, and harassed employees who are later found assaulted or killed at a location remote from the workplace, often represent overlooked instances of workrelated violence.…”
Section: The Context Of Work-related Violencementioning
confidence: 99%
“…It is suggested that work-related violent acts are vastly understated since, in many cases, the figures do not reflect verbal, indirect and passive forms of aggression which are, in fact, more pervasive. [12][13][14] In the UK only those incidents which involve physical violence resulting in at least three days' absence from work are reportable. 15 Keyes and Heim 16 suggest that ambiguous incidents such as an employee who is berated in front of peers, sabotaged machinery which unintentionally injures an employee, and harassed employees who are later found assaulted or killed at a location remote from the workplace, often represent overlooked instances of workrelated violence.…”
Section: The Context Of Work-related Violencementioning
confidence: 99%
“…In a global approach to society, Elliot and Jarrett (1994) refer to the potential role played by the economic climate and multicultural situations.…”
Section: Causes Linked To the Societymentioning
confidence: 99%
“…The extent of the economic prejudice to organizations caused by acts of violence is difficult to evaluate. While direct economic and material prejudice can be calculated (Walter, 1993), it is hardly possible to anticipate it and hence neither to calculate all of the long-term and indirect effects on the organization, nor to anticipate all of the psychological and health-related consequences that a violent act will have on the individual concerned (Brakel, 1998;Elliot and Jarrett, 1994). The costs following a reduction in productivity due to psychological traumas, which still persist, can be considerable (Jenkins et al, 1992).…”
Section: Consequences Concerning the Organizationmentioning
confidence: 99%
“…Les regards posés sur la violence au travail demeurent généralement assez « disciplinaires » ou, tout au moins, plutôt partiels. Certains auteurs s'intéressent, par exemple, aux facteurs qui rendent un individu violent Crawford, 1997 ;Kelleher, 1996 ;Capozzoli et McVey, 1996 ;Elliott et Jarrett, 1994 ;Baron, 1993), quelques-uns s'attardent à des dimensions interpersonnelles telles l'envie ou la jalousie (Neuman et Baron, 2003 ;Vecchio, 2000 ;Andersson et Pearson, 1999) alors que d'autres posent un regard sur les dimensions organisationnelles associées au phénomène (Hoel et Salin, 2003 ;Soares, 2002 ;Lord, 1998 ;Mayew et Quinlan, 1999 ;Neuman et Baron, 1998 ;Einarsen et Raknes, 1997 ;Leymann, 1996 ;Spratlen, 1995 ;Johnson et Indvik, 1994 ;Björkqvist et coll., 1994 ;Diaz et McMillin, 1991). Rares sont ceux, cependant, qui posent un regard plus intégrateur sur le phénomène (Salin, 2003).…”
Section: La Problématiqueunclassified